EDUCATIONAL ORIENTATIONS OF PROVINCIAL YOUTH - Elnikova, Galina; Laamarti, Yuliya; Zhukova, Galina; Boykova, Galina; Gorbunov, Alexandr (Revista Inclusiones, 2020)
Based on the results of an empirical study, the article presents an analysis of educational orientations of the youth residing in the Belgorod and Kursk regions, Russia and describes its specific characteristics. The place of education in the life plans of youth and the role they assign to the education perceived as a life value are noted. The main educational trajectories characteristic of provincial youth in recent years are identified. The significance of the territorial choice of a place of study for provincial youth is demonstrated. The consequences of educational migration for the social status of youth and the regional socio-economic situation are analyzed.